2014
DOI: 10.1186/2193-1801-3-22
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the digestive system of the Octopus bimaculatus paralarvae (Verril, 1883)

Abstract: The high mortalities registered in the larval stage during octopus culturing are mainly due to nutritional deficiencies of the food provided. To understand the cause of this problem, we studied the ontogenetic development of the digestive system of Octopus bimaculatus paralarvae. An egg batch was obtained from a gravid female collected in the Bay of Los Angeles, Baja California, Mexico, and it was incubated in the laboratory during the summer of 2011. We observed that the formation of the digestive system bega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Appearance of pepsin activity at hatching (0 DAH) was observed in the current study, and this is generally reported in various fish species (Perez‐Casanova et al., ; Wang et al., ). Some squids, such as O. bimaculatus , have already formed the organs involved in food ingestion and digestion at 1 DAH although it is not possible to know their actual functionality (López‐Peraza, Hernández‐Rodríguez, & Barón‐Sevilla, ). Observed pepsin activities in the newly hatched paralarvae in the current study are in agreement with the practiced feeding at 48 hr (Lee et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Appearance of pepsin activity at hatching (0 DAH) was observed in the current study, and this is generally reported in various fish species (Perez‐Casanova et al., ; Wang et al., ). Some squids, such as O. bimaculatus , have already formed the organs involved in food ingestion and digestion at 1 DAH although it is not possible to know their actual functionality (López‐Peraza, Hernández‐Rodríguez, & Barón‐Sevilla, ). Observed pepsin activities in the newly hatched paralarvae in the current study are in agreement with the practiced feeding at 48 hr (Lee et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the digestive system functionality of cephalopods in paralarval stages is poorly known. There are only a few studies concerning the development of the digestive system in cephalopod hatchlings (Moguel et al, 2010 ; Martinez et al, 2011 ; López-Peraza et al, 2014 ). The nutritional requirements in the larval stages are critical in aquaculture (Mangetti, 2006 ).…”
Section: Introductionmentioning
confidence: 99%